A Pragmatic Analysis of Using Materials from The Movie Script Wicked (2024) in Teaching Pragmatics: Conversational Implicatures - Amelia Pramais Sella; Malikatul Laila (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Conversational implicature is important to study because it helps people understand the implied meanings in conversation. Therefore, this study aims to describe the use of conversational implicatures found in movie script Wicked (2024) and the results can be used as a source of pragmatic teaching materials for undergraduate students. The focus of this study includes identifying types of implicatures, and forms of flouting conversational maxims in the movie script Wicked (2024). Methodology: This study used qualitative descriptive method. The data source is all dialogue in movie script Wicked (2024) that contains implied meanings or flouting of conversational maxims. Data collection techniques were carried out using reading and note taking techniques while data analysis was conducted by using Grice's (1975) theory of cooperative principle, which focuses on types of implicature and forms of flouting conversational maxims. Results: This study examined 36 utterances and identified two types of conversational implicatures: generalized and particularized, with generalized implicature dominating the findings at 52.8%, meaning that most of the implied meanings can be understood without specific context. In addition, four form of flouting conversational maxims were found, namely flouting maxim of Quantity, Quality, Manner, and Relation, with flouting of quantity dominating the findings at 33.3%, illustrates that characters in the movie provide excessive or insufficient information to convey a particular meaning.Applications/Originality/Value: The results of this analysis can be used as authentic teaching materials in pragmatic teaching. Thus, this study not only enriches pragmatic studies but also provides an interesting alternative learning medium.